2022
DOI: 10.1002/jcv2.12099
|View full text |Cite
|
Sign up to set email alerts
|

Preschool development, temperament and genetic liability as early markers of childhood ADHD: A cohort study

Abstract: Background: ADHD is associated with multiple adverse outcomes and early identification is important. The present study sets out to identify early markers and developmental characteristics during the first 30 months of life that are associated with ADHD 6 years later. Methods: 9201 participants from the prospective Avon Longitudinal Study of Parents and Children (ALSPAC) birth cohort were included. Outcome measures were parent-rated ADHD symptom scores (Strengths and Difficulties Questionnaire, SDQ) and ADHD di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…12 A few more early markers have already been identified, including poor neurocognitive and executive functions, 13 delays or deficits in qualitative features of motor development (fine and gross), 14,15 temperamental activity, and vocabulary delay. 16 Findings from a recent meta-analysis indicate that multiple neurocognitive and behavioral alterations are involved in the early development of ADHD, with the most significant effect sizes found for sensory processing, activity level, and aspects of executive function (inhibition, flexibility, planning/organization, intraindividual variability, impulsivity, and global executive function). 6 However, it may be suggested that these areas reflect (or are similar to) ADHD symptoms, and a broader perspective, including focus on earlier developmental symptoms, is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…12 A few more early markers have already been identified, including poor neurocognitive and executive functions, 13 delays or deficits in qualitative features of motor development (fine and gross), 14,15 temperamental activity, and vocabulary delay. 16 Findings from a recent meta-analysis indicate that multiple neurocognitive and behavioral alterations are involved in the early development of ADHD, with the most significant effect sizes found for sensory processing, activity level, and aspects of executive function (inhibition, flexibility, planning/organization, intraindividual variability, impulsivity, and global executive function). 6 However, it may be suggested that these areas reflect (or are similar to) ADHD symptoms, and a broader perspective, including focus on earlier developmental symptoms, is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Preschool age constitutes a significant time for the initial onset of mental health problems, which often accompany and impact individuals throughout their lives 26 , 27 . The most common mental health presentations in childhood include emotional (e.g., anxiety disorder: childhood prevalence 5.2%) 28 , 29 and behavioral difficulties (e.g., attention-deficit/hyperactivity disorder: childhood prevalence 3.7%) 28 , 30 . Preschool prevention and intervention programs often involve the strengthening of SEC 31 as it serves as an important resilience factor against psychological distress 32 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Tobarra-Sanchez et al (2022) andRiglin et al (2022) discuss their main findings in context of three important limitations. These limitations are important to address in future research as they constrain a broader use of PRS in psychiatric research and clinical contexts.First, PRS for ADHD and other neurodevelopmental conditions at present explain only a small fraction of variance in ADHD and early manifestations of ADHD, and is therefore a weak instrument.While larger GWAS samples will increase the predictive ability, ADHD PRS will likely never, on their own, be able to predict future diagnoses in a meaningful way.…”
mentioning
confidence: 99%
“…Nevertheless, it is possible that PRS in the future, through larger sample sizes and phenotypic refinement, could be used to improve outcome prediction and aid clinical decision-making, together with other clinical variables. As suggested byTobarra-Sanchez et al (2022), future research needs to explore whether predictive models incorporating aspects of early development and PRS are useful for predicting ADHD in clinical practice.…”
mentioning
confidence: 99%
See 1 more Smart Citation